The houses of arrows are numbered consecutively from 1 to 49. Show that there is a value of x such that the sum of the number of houses preceding the house number x is equal to the sum of the number of the houses following it. Find the value of x.
Answer
Verified
473.1k+ views
Hint: In this question, we will first write the house number and find that the numbering is forming an AP whose common difference is 1. After this we will write the sum of house number before house x and sum of house numbers after house x and then equate them to get the equation.
Complete step-by-step answer:
In this question we are going to find the value of x.
Let there be a value of x such that the sum of the number of the houses preceding the house numbered x is equal to the sum of the numbers of the houses following it .
The house number is 1, 2 , 3 …………….x-1,x, x+1……….49.
So, we have a sum of numbers from 1 to x-1 = sum of numbers from x+1 to 49.
Now it is clear from the above data that house number will form an A.P whose
First term and the common difference is 1.
Now we know that the Sum of n terms of an AP is given as:
${{\text{S}}_n} = \dfrac{n}{2}\left( {2a + \left( {n - 1} \right)d} \right)$ , where
n = number of terms in AP.
a = first term of AP.
d= first term of AP.
Let ${S_1}$ be the sum of numbers from 1 to x-1.
${S_1}$= 1+2+3+........+x-1.
Here a =1, d = 1 and n= x-1.
Putting these values in formula of sum, we get:
${{\text{S}}_1} = \dfrac{{x - 1}}{2}\left( {2 \times 1 + \left( {x - 1 - 1} \right)1} \right) = \dfrac{{x(x - 1)}}{2}$
Let ${S_2}$ be the sum of numbers from x+1 to 49.
${S_2}$= (x+1) + (x+2) +........+48+49.
Here a =x+1, d = 1 and n= 49-(x+1)+1=49-x.
Putting these values in formula of sum, we get:
${{\text{S}}_2} = \dfrac{{49 - x}}{2}\left( {2 \times (x + 1) + \left( {49 - x - 1} \right)1} \right) = \dfrac{{(49 - x)(x + 50)}}{2}$
Now according to question:
${S_1}$=${S_2}$
Putting the values of ${S_1}$and ${S_2}$in above equation, we get:
$\dfrac{{x(x - 1)}}{2}$ =\[\dfrac{{(49 - x)(x + 50)}}{2}\]
On further solving , we get:
$ \Rightarrow {x^2} - x = 49x + 2450 - {x^2} - 50x$
$ \Rightarrow {x^2} - x = 2450 - {x^2} - x$
Taking all terms on LHS, we get:
$ \Rightarrow 2{x^2} = 2450$
$ \Rightarrow {x^2} = \dfrac{{2450}}{2} = 1225$
On taking square root on both sides, we get:
$x = \sqrt {1225} = 35$
Hence the value of x which is satisfying our given question is 35.
Note: In this type of question, you should follow the information given the question and then use the result of the AP or GP according to the type of sequence. You should remember the formula for nth term of AP which is given as:
${T_n}$ =a+(n-1)d, where, a is first term , n is value of nth term and ‘d’ is a common difference.
Complete step-by-step answer:
In this question we are going to find the value of x.
Let there be a value of x such that the sum of the number of the houses preceding the house numbered x is equal to the sum of the numbers of the houses following it .
The house number is 1, 2 , 3 …………….x-1,x, x+1……….49.
So, we have a sum of numbers from 1 to x-1 = sum of numbers from x+1 to 49.
Now it is clear from the above data that house number will form an A.P whose
First term and the common difference is 1.
Now we know that the Sum of n terms of an AP is given as:
${{\text{S}}_n} = \dfrac{n}{2}\left( {2a + \left( {n - 1} \right)d} \right)$ , where
n = number of terms in AP.
a = first term of AP.
d= first term of AP.
Let ${S_1}$ be the sum of numbers from 1 to x-1.
${S_1}$= 1+2+3+........+x-1.
Here a =1, d = 1 and n= x-1.
Putting these values in formula of sum, we get:
${{\text{S}}_1} = \dfrac{{x - 1}}{2}\left( {2 \times 1 + \left( {x - 1 - 1} \right)1} \right) = \dfrac{{x(x - 1)}}{2}$
Let ${S_2}$ be the sum of numbers from x+1 to 49.
${S_2}$= (x+1) + (x+2) +........+48+49.
Here a =x+1, d = 1 and n= 49-(x+1)+1=49-x.
Putting these values in formula of sum, we get:
${{\text{S}}_2} = \dfrac{{49 - x}}{2}\left( {2 \times (x + 1) + \left( {49 - x - 1} \right)1} \right) = \dfrac{{(49 - x)(x + 50)}}{2}$
Now according to question:
${S_1}$=${S_2}$
Putting the values of ${S_1}$and ${S_2}$in above equation, we get:
$\dfrac{{x(x - 1)}}{2}$ =\[\dfrac{{(49 - x)(x + 50)}}{2}\]
On further solving , we get:
$ \Rightarrow {x^2} - x = 49x + 2450 - {x^2} - 50x$
$ \Rightarrow {x^2} - x = 2450 - {x^2} - x$
Taking all terms on LHS, we get:
$ \Rightarrow 2{x^2} = 2450$
$ \Rightarrow {x^2} = \dfrac{{2450}}{2} = 1225$
On taking square root on both sides, we get:
$x = \sqrt {1225} = 35$
Hence the value of x which is satisfying our given question is 35.
Note: In this type of question, you should follow the information given the question and then use the result of the AP or GP according to the type of sequence. You should remember the formula for nth term of AP which is given as:
${T_n}$ =a+(n-1)d, where, a is first term , n is value of nth term and ‘d’ is a common difference.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE